Partisan Politics, Civic Priorities, and the Urban Militia: Situating the Calgary Armoury, 1907-1917 - Lackenbauer, P. (Urban History Review / Revue d'histoire urbaine, 2005)
The military's physical presence in Canadian cities has received little critical analysis in terms of local power and identities, urban governance, and competing visions for the use of public space. Using the case study of Calgary, this paper explores the political power struggle surrounding the establishment of an armoury in the early twentieth century. Decision-making involved municipal, provincial, and federal stakeholders, as well as local interest groups, concerned citizens, and the partisan press. This attempt to situate the military within urban political and public space reveals complex processes and relationships, even during an era characterized as “the moment of Canadian militarism.”